Annual Report on China$1 (Bs Economic Growths Macroeconomic Trends and Outlook - Zhang, Ping.; Liu, Xiahui; Yuan, Fuhua; Zhang, Ziran; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book probes into China's economic growth in 2013 and predicts China's development prospects. China$1 (Bs GDP growth in 2014 continues to slow down, and is expected to be 7.6%, with the CPI stable at a level of 2.5%. With the pressures of structural slowdown, 2014 will be a year of adjustment, and there will be a slowdown in new initiatives to minimize risk. Against a background of policies to stabilize growth, change structures and promote reforms, and in order to assess the sustainability of development and transformation and upgrade of China's provincial regions, this book proposes a system for evaluating the country$1 (Bs development prospects and expounds economic growth at the provincial level.s
General Report -- Studies on Macro Economy -- Report of Regional Economic Development Prospects.
Keywords: Macroeconomics; Economic policy; Economic growth; Economics; Macroeconomics/Monetary Economics//Financial Economics; Economic Growth; Economic Policy; Electronic books